A process model for designing information visualization - Akanmu, Semiu A.; Jamaludin, Zulikha (2017)
Information Visualization (InfoVis) employs interactive visuals, graphical presentation, and exploratory data analysis abilities to actualize actionable data insights that are both task and user-centred.In delivering user-centred design (UCD) in InfoVis, studies have been conducted and different but similar UCD models have been proposed. However, these studies, though consist of prototyping, did not elaborately describe the prototyping phase, especially into its constituent stages. As a result of this, InfoVis designers are not armed with a dependable process model of translating InfoVis conceptual design framework to its corresponding physical artifact.To attend to this, we adapted Soukup and Davidson’s (2002) visual data mining project methodology and Rogers, Sharp & Preece’s (2010) software product engineering model to propose an iterative process model for designing InfoVis.The proposed process model was evaluated using expert review. Also, it was used as design guide in prototyping our students’ data-focused InfoVis; StudentViz. The findings from the expert review and the actualization of our InfoVis prototype showed that the proposed process model is functional and practicable.